In situ electrochemical transformation of Ni3S2 and Ni3S2-Ni from sheets to nanodisks: towards efficient electrocatalysis for hydrogen evolution reaction (HER) - Busupalli, Balanagulu; Battu, Shateesh; Haram, Santosh K.; Bhagavatula L. V. Prasad (Chemistryselect, 2016)
Transition metal sulphides have been viewed as alternatives to platinum based electrocatalysts for HER. Herein, we report the preparation of Ni3S2 in conjunction with Ni in a novel nanosheet morphology and verified its performance for HER. During cyclic polarization, exotic morphological transformation of Ni-3 S-2-Ni from nanosheets to nanodisks has been noted. This change is accompanied with initial increase in over-potential that passed through maxima (similar to 100mV above the starting potential) and decreased to similar to 50mV below the starting value. Enhanced electrocatalytic activity due to the morphological changes from sheets to nanodisks has been attributed to the formation of more number of exposed edge-planes known to promote HER. Kinetic analysis based on Tafel slope displayed by this composite is comparable to that of Pt based catalysts.

Rapid and efficient sequestration of arsenic from contaminated water using hypertolerant Bacillus L-148 sp.: a two-step process - Bagade, Aditi; Nandre, Vinod; Ghosh, Sayanti; Battu, Shateesh; Haram, Santosh; Giri, Ashok; Kodam, Kisan (Green Chemistry, 2019)
A fast, robust and green bioreactor for arsenic sequestration from contaminated water was designed. In the two-tier bioreactor, bacterial arsenite detoxification (1 mM) was carried out followed by precipitation of arsenate in 5 min. The precipitate could be used for supercapacitor applications. This bioreactor yielded arsenic free water, therefore, this method can be adopted for scale-up. The combination of hypertolerant bacteria and fast precipitation indicates the robustness of this pilot bioreactor.